Formation of translation competence in future vocational specialists : a systematic review - Dudina, O.; Holovko, I.; Chernyshenko, I.; Дудіна, О.; Головко, I.; Чернишенко, І. (Grupo Editorial Espacios GEES, 2021)
The integration of Ukrainian national higher education system into the global higher education and research space requires targeted reform of higher education in order to ensure its competitiveness. The priority of the development of higher education in Ukraine isthe training of highly qualified, professionally competent professionals who are capable ofself-realizing in the modern information society, are ready for continuous improvement and professional self-development. Modern scientific and technological progress is necessary for the socio-economic and cultural development of humankind, and its achievements must be available for use by representatives of different languages and cultures. An important role of technical translation specialists is to ensure access to modern advanced scientific and technical knowledge from around the world without language barriers. Thus, the issue of professional training of highly qualified, competitive and intellectually developed specialists in technical translation in the world and, in particular, in Ukraine becomes especially relevant. The scientific, technical and economic potential of the United States as a highly developed country has led to interest in studying the experience of this leading country in higher education in the training of technical translators in high-ranking US universities.
Keywords: vocational translation; technical translation; masters preparedness; US Universities